Calibration of High-Frequency Reflectivity of Sediments with Different Grain Sizes Using HF-SSBP - Shuai Xiong; Xinghui Cao; Zhiguo Qu; Dapeng Zou; Huancheng Zhen; Tong Zeng (Journal of Marine Science and Engineering)
Accurate and efficient acquisition of the acoustic reflection properties of sediments with different grain sizes is key for sediment substrate classification and the construction of seafloor acoustic scattering models. To accurately measure surface sediments on the seafloor, an in-depth investigation of the acoustic properties of sediments with different grain sizes at different measurement distances is an indispensable prerequisite. While previous studies have extensively explored the acoustic reflection properties of sediments in mid- and low-frequency bands (e.g., 6–85 kHz), research on high-frequency reflectivity (95–125 kHz) remains limited. Existing equipment often suffers from large beam angles (e.g., >10°), leading to challenges in standardising laboratory measurements. To this end, we developed a technique using a high-frequency submersible sub-bottom profiler (HF-SSBP) to measure the high-frequency reflection intensity of homogeneous sediments screened by grain size. To ensure stable measurements of the high-frequency reflection intensity, we conducted experiments using standard acrylic plates. This demonstrates the dependability of the HF-SSBP and determines the absolute measurement error of the HF-SSBP. Variations in radiofrequency reflection intensity across different sediment types with different grain sizes in a frequency range of 95–125 kHz were investigated. The reflectance amplitude was measured and the reflectance coefficients were calculated for six uniform sediments with different grain sizes ranging from 0.1–0.3 to 2.0–2.5 mm. The scattering intensity of the six sediments with a uniform grain size distribution at the same measurement distance varies to some extent. There is variation in the intensity of acoustic wave reflections for different grain sizes, but some of the differences are not statistically significant. The dispersion coefficients of the acoustic reflection intensities for all sediments, except for those with a grain size of 1.0–1.5 mm, are less than 5% at different measurement distances. These coefficients are almost independent of the detection distance.